Expression analysis of zinc-metabolizing enzymes in the saliva as a new method of evaluating zinc content in the body: two case reports and a review of the literature - Ken-ichiro Sakata; Ayako Hashimoto; Taiho Kambe; Jun Sato; Noritaka Ohga; Yutaka Yamazaki; Masahide Koyachi; Itagaki Tatsuki; Mai Okada; Okura Taro; Hiroshi Hikasa; Yoshimasa Kitagawa (Journal of Medical Case Reports, 2024)
Abstract Background The activity level of alkaline phosphatase, a zinc-requiring enzyme in the serum, is used to indicate zinc nutritional status; however, it does not correlate with serum zinc levels or subjective symptoms of taste disorder in many cases. Hence, this study focused on the total activity of alkaline phosphatase, a zinc-requiring enzyme. The total alkaline phosphatasa activity level in the saliva was measured before and after zinc supplementation, and the results were compared with serum zinc levels. Case presentation This study included patients with hypozincemia, specifically a patient with zinc-deficient taste disorder (patient 1: a 69-year-old Japanese woman) and a patient with glossodynia with zinc deficiency (patient 2: an 82-year-old Japanese woman). Saliva samples were collected, and blood tests were performed before and after zinc supplementation. Subjective symptoms and serum zinc levels were simultaneously evaluated. Zinc supplementation was performed using zinc acetate hydrate or Polaprezinc. Conclusions Total alkaline phosphatase activity levels were found to be associated with serum zinc levels and subjective symptoms. A further study with a higher number of patients is necessary to confirm whether total alkaline phosphatase activity levels more accurately reflect the amounts of zinc in the body than serum zinc levels.